IMMUNE STATUS OF PATIENTS WITH GRADE III IDIOPATHIC GONARTHROSIS - I. A. Mamonova; O. A. Kauts; Yu. A. Barabash; S. P. Shpinyak; K. A. Grazhdanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Objective: to analyze some parameters of cellular and humoral immunity and peripheral blood cytokines in patients with grade III idiopathic gonarthrosis, as well as to identify most significant laboratory immunological  tests indicating the activity of articular tissue degradation. Materials and methods. We assessed laboratory parameters reflecting the immune status in 20 patients with grade III idiopathic gonarthrosis (18 males and 2 females; mean age 64.1 years (range 58.6; 62.1 years). Results. We observed some immunological changes in peripheral blood of patients with grade III gonarthrosis, such as a decrease in the T cell count (T-helpers and T-suppressors), B cell count, and in the level of immunoglobulins G along with an increase in the count of natural killers, levels of serum immunoglobulin A, and proinflammatory (TNFa, IL-6) and antiinflammatory (IL-10, IL-4)  cytokines. Conclusion. Degenerative dystrophic changes in the knee joint affect the immune status of patients with grade III gonarthrosis. It is necessary to evaluate parameters of cellular and humoral immunity of patients with advanced gonarthrosis before surgical interventions in order to minimize the risks of early and late postoperative  complications.